ORONYMS WITH A ZOONYMIC COMPONENTS IN THE ORONYMIC SYSTEM OF BOYSON DISTRICT (Scientific journal of the Fergana State University, 2026)
This article is devoted to the linguistic analysis of the oronymic system of Boysun district, specifically investigating oronyms that contain a zoonymic component (animal names), referred to as zoooronyms. Examples demonstrate that the emergence of these names is linked to natural factors (animal habitation, resemblance of the oronym’s shape to an animal), cultural and mental characteristics (totemism, national games), as well as the observations of the local population. According to the research results, zoooronyms constitute 10% of all oronyms in Boysun district. They are classified into four groups based on the names of domestic animals (Otguzar, Aygʻirtepa), wild animals (Qoplondara, Tulkixona), birds (Laylakxona, Gʻajirqoya), and insects (Qoʻngʻizbuloq). The analysis indicates that, due to the mountainous nature of the region, the majority of zoooronyms are associated with wild animals. The article provides etymological and semantic explanations for oronyms such as Otchopar, Doʻltaxona, Aygʻirtepa, Xukparida, Tangimush, and Koʻppak tepa. In conclusion, oronyms are historical codes, and their study is of great importance for linguistics, historical geography, and ethnography.